2021
DOI: 10.1093/nar/gkab937
|View full text |Cite
|
Sign up to set email alerts
|

ASMdb: a comprehensive database for allele-specific DNA methylation in diverse organisms

Abstract: DNA methylation is known to be the most stable epigenetic modification and has been extensively studied in relation to cell differentiation, development, X chromosome inactivation and disease. Allele-specific DNA methylation (ASM) is a well-established mechanism for genomic imprinting and regulates imprinted gene expression. Previous studies have confirmed that certain special regions with ASM are susceptible and closely related to human carcinogenesis and plant development. In addition, recent studies have pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 56 publications
(51 reference statements)
0
19
0
Order By: Relevance
“…Increased methylation of MITEs, located upstream or downstream of a coding region, can also repress or activate gene expression (Xu et al ., 2020). In this study, based on the methylation data from the Allele‐Specific DNA Methylation Database (ASMdb; Zhou et al ., 2022), we found that the MITE region of the HTG3 promoter was hypermethylated compared with neighboring regions, suggesting that the suppression of HTG3a may be a result of increased DNA methylation in the promoter.…”
Section: Discussionmentioning
confidence: 79%
“…Increased methylation of MITEs, located upstream or downstream of a coding region, can also repress or activate gene expression (Xu et al ., 2020). In this study, based on the methylation data from the Allele‐Specific DNA Methylation Database (ASMdb; Zhou et al ., 2022), we found that the MITE region of the HTG3 promoter was hypermethylated compared with neighboring regions, suggesting that the suppression of HTG3a may be a result of increased DNA methylation in the promoter.…”
Section: Discussionmentioning
confidence: 79%
“…The young group had 18 aDMRs and the adult group had 13 aDMRs. Previously, Zhou et al [ 24 ] reported 24,557 allele-specific expressed genes (ASEGs) of 91 human tissues and cell lines of the allele-specific DNA methylation database. Of these 24,557, five genes were shared with our 15 aDMR-related genes in the thymus, which were U6 , ZNF287 , PELO , ZNF596 and NUPR2 .…”
Section: Resultsmentioning
confidence: 99%
“…Allele specific gene expression data for IMR-90 and H1-hESC were obtained from the UCSD Human Reference Epigenome Mapping Project (Kundaje et al ., 2015) via the ASMdb (Zhou et al ., 2022). Allele specific expression data for GM12878 were obtained from previously published work (see SI Table 2) (Workman et al ., 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The filtered gene list was merged with Ensembl IDs from Gencode v38. ASEG data for IMR90 and H1-hESC were obtained from the UCSD Human Reference Epigenome Mapping Project (Kundaje et al, 2015) via the ASMdb (Zhou et al, 2022).…”
Section: Data Availabilitymentioning
confidence: 99%